Near perfect and polarization insensitive broadband absorber based on Al2O3 - Ti - Al2O3 triple layer structure. (1st February 2023) - Meng, Qiqi; Chen, Fang; Cheng, Shubo; Xu, Yiping; Yang, Wenxing; Yi, Zao
Abstract: In this paper, a polarization-insensitive and broadband absorber based on Al 2 O 3 - T i - Al 2 O 3 rectangular periodic sandwich structure has been studied. Simulations indicate the absorbance remains over 97% at the wavelength from 599 nm to 1912 nm, and the corresponding average absorption is up to 98.5% in this range. Moreover, the broadband absorption is background refractive index and polarization insensitive. The absorption mechanism of the broad-band is studied by impedance-matching theory and finite difference time domain (FDTD) method, which is mainly originated from the cavity plasmonic resonance, surface plasmonic dipolar resonance, and near field plasmonic coupling effect. The proposed broadband absorber is expected to play a role in solar cell, which can be applied in the areas of solar cell design, imaging, and thermal emitters. Moreover, the use of Ti material and Al 2 O 3 instead of noble metals has the advantages of thermal robustness, and lower cost.